2020
DOI: 10.1101/2020.06.28.176198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shotgun scanning glycomutagenesis: a simple and efficient strategy for constructing and characterizing neoglycoproteins

Abstract: AbstractN-linked glycosylation serves to diversify the proteome and is crucial for the folding and activity of numerous cellular proteins. Consequently, there is great interest in uncovering the rules that govern how glycosylation modulates protein properties so that the effects of site-specific glycosylation might eventually be predicted. Towards this goal, we describe a combinatorial strategy termed shotgun scanning glycomutagenesis (SSGM) that enab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…Recent computational studies have demonstrated new ways to explore protein-carbohydrate interactions. Our lab has also contributed to the advancement of this field by adding the following, (1) a shotgun scanning glycomutagenesis protocol to predict the stability and activity of protein glycovariants (23), and (2) the GlycanDock algorithm to refine protein-glycoligand bound structures (24).…”
Section: Introductionmentioning
confidence: 99%
“…Recent computational studies have demonstrated new ways to explore protein-carbohydrate interactions. Our lab has also contributed to the advancement of this field by adding the following, (1) a shotgun scanning glycomutagenesis protocol to predict the stability and activity of protein glycovariants (23), and (2) the GlycanDock algorithm to refine protein-glycoligand bound structures (24).…”
Section: Introductionmentioning
confidence: 99%